SISTEM PENDUKUNG KEPUTUSAN PENILAIAN SISWA MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING BERBASIS FRAMEWORK LARAVEL - Amrizal, Amrizal; Tukino, Tukino; Harman, Rika (Universitas Putera Batam, 2022)
The assessment of student learning outcomes is a mandatory process in educational institutions, whether they are formal or non-formal, with the aim of monitoring and evaluating student progress during the learning process. With the advancement of technology, there are many processes that can be integrated with information technology to simplify existing procedures. The purpose of this research is to facilitate schools in making decisions regarding the results of the learning assessment process by using predefined attributes. The attributes used as reference for consideration are assignments, mid-term exams (UTS), and final exams (UAS). Therefore, this study is built using the SAW method and the PHP programming language supported by the Laravel framework. The output of this research is an information system that supports decision-making in assessing student learning outcomes in the form of subject rankings and provides transparency and convenience for students to access their grades or the final results of the student learning assessment process.